2018
DOI: 10.1159/000492253
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Activity of Combined Use of Caffeic Acid with Paclitaxel Enhances Apoptosis of Non-Small-Cell Lung Cancer H1299 Cells in Vivo and in Vitro

Abstract: Background/Aims: Caffeic acid (CA) is known to possess multiple biological activities including anti-cancer activities. However, the molecular mechanisms underlying these activities in non-small-cell lung cancer (NSCLC) cells are not fully understood. We attempted to clarify whether CA could enhance paclitaxel (PTX)-induced cytotoxicity in H1299 cells. Methods: First, we tested the cytotoxic effects in both H1299 cells and normal human Bease-2b cells by cell proliferation experiments. Next, we use Annexin V/pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 33 publications
(37 reference statements)
5
37
0
Order By: Relevance
“…21 Increased expressions of phosphorylated JNK, ERK 1/2, and p-38 proteins with increasing concentration of matricin in the western blot analysis proved that matricin triggered apoptosis in H1299 cells through activation of MAPK pathway. The results of MAPK pathway activation are similarly described in the findings of Min et al 17 Overall, matricin has shown significant anti-proliferative and apoptosis-inducing effects in non-small cell lung cancer H1299 cells. Limitations in this study are the detailed mechanism of apoptosis inducing and the specific small molecule markers responsible for apoptosis were not determined.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…21 Increased expressions of phosphorylated JNK, ERK 1/2, and p-38 proteins with increasing concentration of matricin in the western blot analysis proved that matricin triggered apoptosis in H1299 cells through activation of MAPK pathway. The results of MAPK pathway activation are similarly described in the findings of Min et al 17 Overall, matricin has shown significant anti-proliferative and apoptosis-inducing effects in non-small cell lung cancer H1299 cells. Limitations in this study are the detailed mechanism of apoptosis inducing and the specific small molecule markers responsible for apoptosis were not determined.…”
Section: Discussionsupporting
confidence: 78%
“…The western blot analysis was performed according to the protocols of Min et al 17 The H1299 cells were pre-treated with matricin (0-80 µM) for 24 h, harvested, and thoroughly rinsed with cold PBS, and centrifuged to obtain cell lysate proteins. Proteins were extracted in radioimmunoprecipitation assay (RIPA) buffer, and immunoblotting was performed using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gel electrophoresis.…”
Section: Western Blot Analysis For Mapk Pathway Determination In Apopmentioning
confidence: 99%
“…Even though, preceding researches have indicated the effi cacy of CA in inhibiting the viability of cancer cells (Cai et al, 2004, Ishida et al, 2018, Min et al, 2018, this study has pointed out the infl uences of CA in H 2 O 2 -treated HT-29 cells probably to go back to the mismatching results in cancer studies. Davison et al, (2013) and Park (2013) independently reported a controversial information on the infl uence of antioxidant supplement on cancerous cells which was in confl ict with the outdated notion that antioxidants ought to serve as a remedy that would decrease the risk for cancer development by scavenging cancer-leading radicals.…”
Section: Discussionmentioning
confidence: 66%
“…Caffeic acid displays antioxidant and anticancer activities [ 123 , 124 , 125 , 126 ], protecting several organs as lungs [ 127 , 128 ], mouth [ 129 , 130 ], liver [ 131 , 132 ], and colon [ 133 , 134 , 135 ]. Caffeic acid can impair macromolecule damage, balancing oxidative stress conditions, and its high antioxidant activity can be ascribed to the hydroxyl groups and the ortho-dihydroxyl group in the caffeic acid molecule [ 136 ].…”
Section: Bioactive Compounds In Beetroot Product Interventionsmentioning
confidence: 99%